Pengaruh Kepercayaan Dan Kesadaran Etika Terhadap Niat Mahasiswa Yang Sudah Bekerja Untuk Menggunakan Kredit Perbankan Syariah - Alya Sakinah; Junaidi Junaidi; Rismawati Rismawati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the relationship between trust and ethical awareness towards the intention of working students in using Islamic banking credit products. Using a survey method, data were collected from students at various universities. The findings indicate that trust in Islamic principles and ethical awareness significantly contribute to the intention of working students to use Islamic banking services. The results highlight the importance of ethical education and understanding of sharia in promoting the use of credit that aligns with religious values. It is hoped that this research can provide insights for financial institutions to formulate more effective marketing strategies. In this study, the data collected came from students. Subsequently, the data were analyzed using SPSS version 16.